A Pd‐Catalyzed Synthesis of Functionalized Piperidines. Issue 37 (5th July 2016) - Allen, Benjamin D. W.; Connolly, Matthew J.; Harrity, Joseph P. A.
Abstract: A readily available cyclic carbamate1 functions as a general precursor to a range of functionalized piperidine products via a new Pd‐catalyzed annulation strategy. An asymmetric catalytic variant provides a rapid and efficient means to access these heterocycles with high to excellent levels of enantiocontrol. Finally, these richly functionalized compounds are amenable to further chemoselective elaboration. Abstract : To cut a long story short… A cyclic carbamate functions as a general precursor to a range of functionalized piperidine products through a new Pd‐catalyzed annulation strategy. An asymmetric catalytic variant provides a rapid and efficient means to access these heterocycles with high to excellent levels of enantiocontrol.